Managerial Competencies: Factors of "Necessity and Sufficiency" in the Description and Explanation of the Phenomenon - Tolochek, Vladimir A.; Mashkova, Anna S. (Saratov State University, 2020)
The study discusses results of the series of studies of competencies and features of their evaluation by managers (69 people) of different gender, age, length of employment, managerial experience, and positions, who are working in different companies. Hypotheses: 1. There are more and less relevant competencies among those that are evaluated as in-demand ones. 2. Competencies, which are evaluated as in-demand ones, are associated with evolution of managers as subjects. 3. Within the structure of managerial in-demand competencies, we can single out groups of qualities that differ in their role in the activities of subjects. Differentiated level-by-level analysis of assessments made by different groups of experts was carried out (analysis of 29 selected competencies; 19 were identified by at least 40% of experts; 8 were identified by at least 66% of experts; analysis of an expanded list of 39 competencies). Experts differed by gender, age, length of managerial work, position, career success, managerial potential, divisions within the company and type of activity ("result managers", "process managers"). Conclusions: Evaluation of relevant (important, significant and/or preferred) managerial competencies vary depending on individual characteristics of experts (gender, age, experience, position, career success, managerial potential). 3. Lists of competencies containing the interval of 15-20 qualities can be considered optimal for solving both scientific and applied problems. The basic list of 29 competencies can be conditionally considered "sufficient and redundant"; the list of up to 19-20 competencies can be considered as "sufficient and necessary"; and the list of 8-10 "nuclear" competencies can be considered as "necessary basic" one. Managers' evaluations of relevant competencies vary depending on professional tasks and forms of work remuneration. Unification of standard forms of remuneration for "process managers" involves the unification of their ideas about relevant competencies; differentiation of the forms of remuneration for "result managers" is associated with an increase in the variability of their ideas about the in-demand competencies of managers.